16‐3: Compact Tunable Alvarez Lens Based on Pancharatnam‐Berry Optical Elements. Issue 1 (28th June 2022) - Lin, Junhao; He, Ziqian; Zhuang, Zhongsen; Li, Yan; Su, Yikai; Wu, Shin-Tson
Abstract : Alvarez lens, whose focal length can be continuously tuned by changing the relative lateral positions of its sub‐elements, holds promise in realizing vari‐ or multi‐focal augmented reality (AR) displays to eliminate vergence‐accommodation conflict and 3D visual fatigue. In this paper, we propose and realize a compact Alvarez lens based on planar Pancharatnam‐Berry optical elements. We also demonstrate an augmented reality display system using the proposed Alvarez lens, which allows virtual objects to appear at different focal depths.